Saturday, 16 JUNE 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.6085
|View full text |Cite
|
Sign up to set email alerts
|

SAT0099 Sarcopenia is associated with joint damage in rheumatoid arthritis: a cross-sectional study

Abstract: BackgroundThe association of metabolic status with disease characteristics of rheumatoid arthritis (RA) remain controversial. Body composition (BC) instead of body mass index (BMI) has been more and more recommended to assess metabolic status.ObjectivesTo investigate the characteristics of BC in RA patients and their association with RA disease characteristics.MethodsBC was assessed in RA patients and control subjects by bioelectric impedance analysis. Overfat was defined by body fat percentage (BF%) as ≥25% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other studies have also observed an association between sarcopenia (defined by muscle mass, SMI) and radiographic joint damage (OR = 2.154; 95% CI 1.032–4.497; p = 0.041) [ 38 ] and bone erosion (OR = 0.057; 95% CI 0.006–0.532; p = 0.012) in patients with RA [ 21 ].…”
Section: Sarcopenia and Immuno-mediated Rheumatic Diseasesmentioning
confidence: 99%
“…Other studies have also observed an association between sarcopenia (defined by muscle mass, SMI) and radiographic joint damage (OR = 2.154; 95% CI 1.032–4.497; p = 0.041) [ 38 ] and bone erosion (OR = 0.057; 95% CI 0.006–0.532; p = 0.012) in patients with RA [ 21 ].…”
Section: Sarcopenia and Immuno-mediated Rheumatic Diseasesmentioning
confidence: 99%